تأثير شدة الإضاءة في إنتاجية الفليفلة ونوعية الثمار في الزراعة المحمية - سمرة, بديع; نداف, محمد; دمسرخو, رامونا (Latakia University Journal -Biological Sciences Series, 2019)
نفذ البحث خلال الموسمين الزراعيين 2009/2008 و2009/2010 في مركز بوقا للبحوث والإنتاج النباتي التابع لكلية الزراعة – جامعة تشرين ضمن بيت بلاستيكي، وتضمنت الدراسة خمس معاملات بأربع مكررات لكل معاملة تم فيها تخفيف شدة الإضاءة بتظليل شرائح الغطاء البلاستيكي بطرائق مختلفة لمعرفة تأثيرها على شدة الإضاءة النافذة إلى داخل البيت البلاستيكي الواصلة لنبات الفليفلة، وذلك بهدف دراسة أثر شدة الإضاءة في نمو وإنتاج نبات الفليفلة ونوعية الثمار تحت ظروف الزراعة المحمية. بينت النتائج أن تقليل شدة الإضاءة خلال أشهر الصيف يؤدي إلى زيادة المسطح الورقي للنبات بين 1448 و 10517 سم²، وزيادة في إنتاجية النبات بين 769و2263 غ/نبات مقارنة مع الشاهد غير المظلل، وهذا يفتح المجال أمام إمكانية الاستفادة من البيوت البلاستيكية على مدار العام. This research was carried out in a greenhouse in Bouka Center for Research and Plant Production, Faculty of Agriculture, Tishreen University over two growth seasons 2008/2009 and 2009/2010. The study included five treatments with four replicates, in which the rate of the light intensity was reduced by shading plastic covers using different methods, to measure its effect on the rate of transmitted light into the greenhouse which reaches to the pepper plant, in order to study the effect of light intensity on the growth and yield of Pepper (Capsicum. annum, L. ) and fruits' quality under greenhouses. This study has shown that, the reducing of light intensity during summer period leads to increasing the plant leaf area from 1448 to 10517 cm², and plant yield from 769 to 2263 g/plant in comparison with non-shaded control. Results of this research open the door widely for using greenhouses all over the year.